2017
DOI: 10.1002/ccd.27392
|View full text |Cite
|
Sign up to set email alerts
|

Carotid‐cavernous fistula after endovascular intervention for chronic carotid artery total occlusion

Abstract: CCF may develop during chronic CAO endovascular recanalization attempts. It is usually self-limited and can be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To understand the indicators that might predict the risk of an iatrogenic CCF complication, some groups have studied the circumstances of these cases at their institutions. Yeh et al studied 138 surgical interventions to treat chronic carotid artery occlusion and observed that 8% of these resulted in a CCF [18]. The instances were self-limiting, and none resulted in stroke or death.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the indicators that might predict the risk of an iatrogenic CCF complication, some groups have studied the circumstances of these cases at their institutions. Yeh et al studied 138 surgical interventions to treat chronic carotid artery occlusion and observed that 8% of these resulted in a CCF [18]. The instances were self-limiting, and none resulted in stroke or death.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles were published from the same institution in Taiwan, we selected one of their papers with the largest number (n=138) of patients for our study (24). Data from two additional papers from this institution were also used to identify perioperative (25,26). The final systematic review included 276 patients from 8 observational studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Endovascular recanalization of chronically occluded ICA was first reported by Terada et al in 2005 (6). Since then, multiple case reports (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) retrospective and prospective cohort studies (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) have been published, most claiming benefit in patients who underwent successful endovascular or hybrid treatment, but no randomized controlled studies are available and society guidelines so far have failed to recommend endovascular therapy for symptomatic CTO of the ICA (29,30). The aim of this systematic review was to investigate patient selection, technical success, periprocedural complications, early and late outcome of endovascular treatment for symptomatic CTO of the ICA.…”
Section: Introductionmentioning
confidence: 99%
“…This was the only complication observed during surgery. CCF was not uncommon when performing endovascular maneuvers in patients with TO; its incidence was approximately 8% [5] . Much attention should be paid when exploring occluded segments, and if CCF occurs, the ICA should be sutured immediately.…”
mentioning
confidence: 99%